Navigating the Artificial Intelligence Frontier: Balancing Innovation with Responsibility - An Ethical Imperative - Chilcott, Glenn (Global journal of Business and Integral Security, 2024)
Artificial Intelligence (AI) presents transformative opportunities, with projections indicating it could contribute up to $15.7 trillion to the global economy by 2030. However, these opportunities are accompanied by significant ethical and regulatory challenges. This paper explores the necessity for robust governance frameworks to ensure responsible AI deployment, addressing issues such as transparency, privacy risks, bias, and corporate power concentration. It emphasizes the importance of integrating ethical considerations throughout the AI lifecycle, transcending mere compliance to foster a culture of integrity and accountability. Through an analysis of classical and contemporary ethical theories, the paper underscores the role of moral responsibility in AI development, asserting that ethical governance is essential for long-term sustainability. Ultimately, the future of AI depends not only on technological innovation but on the ethical decisions made in the present, which will determine whether AI serves societal well-being or exacerbates existing inequalities.